PENDIRIAN PT PENANAMAN MODAL ASING DI INDONESIA - Sri Purwaningsih (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2016)
Foreign investment is one of the ways that must be taken to boost economic growth - in addition to the use of technology, expansion of knowledge, improvement of skills, organizational skills and management. Establishment PT PMA (Foreign Investment PT) starting from the manufacture of ICC (International Chamber of Commerce), which contains the investment policy, ownership and management, financial and fiscal policies, legal framework, labor policy, technology, commercial policy. All of these policies in terms of the parties. Furthermore, all contained within the text ICC poured into a LOI (Letter of Intent) or MOU (Memorandum of Understanding), followed by the manufacture of JVA (JV Agreement) an agreement that contains the will of the parties in more detail, decompose and complete. The next step is the manufacture of incorporation documents with the notary deed containing the articles of association of the company. In the establishment of PT PMA, the position of the parties must be balanced from the establishment to the company's operations.